ON SIN, SILENCE AND OTHERNESS (Annual of the Faculty of Philosophy in Skopje, 2016)
This paper will attempt to explore the connection between sin and silence, as well as the one between sin and worldhood, i.e. otherness, by examening Kierkegaard’s doctrine of sin - and, more specifically, Adam ’s first sin - in The concept of anxiety. It will pursue three interconnected goals. Its first goal is to point out that Kierkegaard’s work puts forth a genuine epistemological framework, which is both idealistic and transcendental. Its second goal will be to show that the fulfillment of Adam ’s sin requires speech, that is, a peculiar kind of dialogue of man with himself; and, at the same time, that such a fulfillment can only take place outside of any relationship with the other. Indeed, Adam ’s original sin is what first establishes all kinds of otherness. Finally, on the basis of previously attained conclusions, its third goal is to demonstrate that the subsuming of original sin under the class of ethical concepts, its characterisation as good or evil, is, at the very least, to be taken cum grano salis.
Keywords: KIERKEGAARD; ANXIETY; ORIGINAL SIN